Monte carlo simulations of relaxor ferroelectric dielectric permittivity in films structure - Laosiritaworn Y. (2014)
In this study, the Monte Carlo simulation was used to investigate relaxor films using the spin-glass Hamiltonian with the surface effect. The single polarization flip algorithm was used to update the local polarizations where the relaxation time was measured to calculate the dielectric permittivity and loss as varying temperature, field frequency and films thickness. From the results, in the vicinity of the electrodes on the topmost and bottommost layers, the relaxor films exhibit thickness-dependent dielectric properties in qualitatively good agreement with experiments. The maximum dielectric permittivity enhances in the films with increasing the films thickness as expected. The relations of how maximum dielectric permittivity and its corresponding temperatures vary with thickness are also explained. Copyright © Taylor & Francis Group, LLC.